GRACE FOR GUS. - BLISS, HARRY ([S.l.] : KATHERINE TEGEN BOOKS, 2018)
Grace is the quiet girl in the class. And Gus is the class guinea pig. Grace knows that Gus is lonely, and so she sets off one night to help out her furry friend. Wherever she goes, Grace amazes and delights as she shares her many talents, showing how one person with a little pizzazz can make a difference.